High-Performance Liquid Chromatographic Assay of Chloramphenicol in Serum - Koup, Jeffrey R. (1978)
A new method for the analysis of serum chloramphenicol by reversed-phase, high-performance liquid chromatography (HPLC) is described. The method involves a preliminary extraction of 0.1 ml of serum with ethyl acetate containing an internal standard, chromatography with a reversed-phase C18 microparticulate column with an acetonitrile-acetate buffer mobile phase, and detection by measuring UV absorbance at 270 nm. Assay performance was compared with an existing microbiological assay. The HPLC method demonstrated both increased precision and increased sensitivity. The specificity of the HPLC method was also evaluated. The new method presents an alternative approach to the analysis of clinical specimens.